(untitled) (Philological Studies, 2020)
The article carries a review of research works on visual stylistic means in advertising. Researchers see them as the means of manipulation that evoke specific associations and assessments in recipients. The main aim of the article is to prove the validity of identification of visual comparison as visual stylistic means. Visual comparison in political advertising is regarded as an ideological means of influence on a global recipient. Visual comparison is in the nature of correlation or opposition and is effectively used in political advertising compared to other visual stylistic means. The correlation includes two images that are used to draw the attention of the addressee to certain socio-political problems, to form a positive image of the candidate and his program. The mean of opposition is based on a comparison of two antagonistic images, which forces the recipient to make a choice in favor of one of them. The obtained results can be used for further development of the theory of visual textual stylistics and for the creation of texts of political Internet advertising.